The level of application of quality assurance bases in the academic department of the faculties of business and finance - Abdul-Raheem Muhammad Qadoomi (University of Science and Technology, Yemen, 2008)
Abstract                                                                                                   This study focused on how to apply the bases of quality assurance accredited by Al Hussein Fund for Excellence, American and Britain quality assurance committees and some academic departments. A comparison between the results of external and internal auditing related to the level of application was made. The comparison revealed the bases components that must be taken care of. For data analysis, the researcher used arithmetic means, standard deviation and T -test. Results reveal that one can depend on internal auditing bodies   to identify weaknesses and strengths along with external ones, as the analysis of the internal reviewer is not less professional, in addition, he knows  better the values and local culture. He is impartial and fully aware that there is a strong relationship between what happens academically and the market as it  is the essence of quality assurance.